2019
DOI: 10.1155/2019/7290852
|View full text |Cite
|
Sign up to set email alerts
|

Transfusional Malaria and Associated Factors at the National Blood Transfusion Center of Niamey-Niger

Abstract: Summary. Problem. Transfusional malaria is an accidental transmission of Plasmodium via a blood transfusion. Its magnitude is underestimated and very little data on the assessment of this risk are available in Niger. Objective. This study aimed to determine the prevalence of plasmodial infection of blood bags at the National Blood Transfusion Center of Niamey (NBTC). Methodology. A cross-sectional study to diagnose Plasmodium infection by microscopy and Rapid Diagnostic Test (RDT) was carried out during the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Among these studies, a significantly lower proportion of malaria among Rh+ individuals was reported by two studies [39,44]. Three studies reported a lower proportion of malaria among Rh+ individuals than in Rh− individuals, though no statistical significance [37,45,48].…”
Section: Reporting Quality Of the Included Studies And Qualitative Sy...mentioning
confidence: 93%
See 4 more Smart Citations
“…Among these studies, a significantly lower proportion of malaria among Rh+ individuals was reported by two studies [39,44]. Three studies reported a lower proportion of malaria among Rh+ individuals than in Rh− individuals, though no statistical significance [37,45,48].…”
Section: Reporting Quality Of the Included Studies And Qualitative Sy...mentioning
confidence: 93%
“…Based on the STROBE criteria, two-thirds of studies (75%) were of moderate quality [22,24,[26][27][28][29][30][31][33][34][35][36][38][39][40][41]43,[45][46][47][48]50,[52][53][54][55]. Meanwhile, eight studies were of high quality (22.2%) [23,25,31,37,42,44,51,56], and one was of low quality (2.78%) [49] (Table S3). The systematic review included all studies, and the varied reporting quality was addressed in the metaregression analysis to investigate whether the different reporting qualities of the included studies affected the combined outcome.…”
Section: Reporting Quality Of the Included Studies And Qualitative Sy...mentioning
confidence: 99%
See 3 more Smart Citations